To Study the Role of Infectious Agents in Gallstones Formation in Different Age Groups - SUMERA ASHFAQ NADIA FAROOQ, HURRIAT AFZAL (Journal of Fatima Jinnah Medical University, 2018)
Background: Gallstone disease remains one of the most common medical problems leading to surgical intervention. Infection plays a role in the development of these stones. Aims and Objectives: Study was designed to find out role of infectious agents in gall stone formation in women with different age groups. Methodology: Case control study of six months was conducted in Surgical Ward of Sir Ganga Ram Hospital Lahore. 100 women with confirmed upper abdominal ultasonography for gall stone diagnosis were included in the study. Patients were divided into 3 groups based on their age range 25-39 years (group 1), 40-50 years (group 2) and > 50 years (group 3). Patients were considered to be in the perimenopausal period, based on irregular menstruation or its cessation, vasomotor symptoms and decreasing estrogen levels. The subjects were not taking any medication, including hormone replacement therapy. Detailed information was filled in proforma. Results: It was observed that the mean age of women belong to group 1 was 31.88 years, of group 2 was 42.29 years and of group 3 was 61.25 years. Their BMI was 26, 26.5 and 28.0 kg/m2 respectively. Mixed type of gall stone (cholesterol and bilirubin) was observed in group 1. On the other hand in group 2 and 3 mixed type of gall stone consist of cholesterol, bilirubin and calcium. Infectious agent like staph aureus and pseudomonas aureginosa were identified in all groups. Conclusion: Both gram positive and gram negative bacteria may play a role in developing gall stone in 35% menstruating women, 49% perimenopausal and 16% postmenopausal women. It is concluded that gall stone formation may be more prevalent in menstrual and perimenopausal age as compared to postmenopausal age.